Relationship between Corporate CEO Succession Planning and Corporate Performance - Zongyi Yin; Jiamei Ye; Xiaoying Wang; Fang Su (Amfiteatru Economic)
In an increasingly competitive market environment, as an important decision for strategic change, CEO succession is a key step to driving sustainable development. The formulation of succession plans and how to improve the effectiveness of internal promotion mechanisms have been researched topics in executive team management. To explore the relationship between corporate executive succession planning and corporate performance, using 3955 CEO succession samples from 2599 companies during 2001-2015 in China, the Probit model, and the two-stage least squares method, the relationship between corporate CEO succession planning and corporate performance under the director-cum-CEO succession model was analysed. The results reveal that the formulation or not of succession plans in firms, particularly in listed firms, directly affects firm performance. Director-CEO internal succession decisions reduce firm performance relative to other CEO succession models. Conclusions obtained from this study indicate the relationship between succession planning and organisational performance at the micro level and provide a theoretical reference to further promote research related to succession decisions in listed companies and the longterm development interests of firms.